Modeling regulatory network topology improves genome-wide analyses of complex human traits - Xiang Zhu (Nature Portfolio, 2021)
Gene regulatory networks are a useful means of inferring functional interactions from large-scale genomic data. Here, the authors develop a Bayesian framework integrating GWAS summary statistics with gene regulatory networks to identify genetic enrichments and associations simultaneously.